2020
DOI: 10.3390/s20164400
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Stress Assessment Using Sliding Window Based Convolutional Neural Network

Abstract: Mental stress has been identified as a significant cause of several bodily disorders, such as depression, hypertension, neural and cardiovascular abnormalities. Conventional stress assessment methods are highly subjective and tedious and tend to lack accuracy. Machine-learning (ML)-based computer-aided diagnosis systems can be used to assess the mental state with reasonable accuracy, but they require offline processing and feature extraction, rendering them unsuitable for real-time applications. This paper pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Reduction in alpha activity is a strong indicator of stress as brain activity in this frequency band reflects relaxed state of consciousness [ 48 , 61 ]. Higher relative power in the alpha band compared to theta and beta bands during resting reflects its dominant role during relaxed consciousness [ 62 ], and has commonly been used as the neuromarker for stress response state [ 6 , 8 , 23 , 25 ]. Change in the alpha activity from high to low indicates increasing alertness and attention to external stimuli, as observed during the VR trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction in alpha activity is a strong indicator of stress as brain activity in this frequency band reflects relaxed state of consciousness [ 48 , 61 ]. Higher relative power in the alpha band compared to theta and beta bands during resting reflects its dominant role during relaxed consciousness [ 62 ], and has commonly been used as the neuromarker for stress response state [ 6 , 8 , 23 , 25 ]. Change in the alpha activity from high to low indicates increasing alertness and attention to external stimuli, as observed during the VR trials.…”
Section: Discussionmentioning
confidence: 99%
“…The electroencephalography (EEG) is the most used brain-monitoring method for mental stress because of its portability, high temporal resolution, non-invasive, and low cost advantages [ 5 ]. The EEG brain waves (0.5–45 Hz) are strongly associated with different brain responses towards stress and have been used to detect stress [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…[51] Visual [52] N/A [53], [54], [55], [56], [57], [58], [59], [60], [61], [45], [33], [62], [63], [64], [65], [66] Depression both mild and severe stages Emotional Note reading [67] Audio [68] Emotional Picture [69], [70], [71], [72] Distractor and target [73] N/A [74], [75], [76], [77], [78], [79], [80], [81], [82], [83], [84], [85], [86], [87], [88] Depression for other reasons (stress/ epilepsy) Audio [89], [90] N/A [91], [92], [93] This…”
Section: Mild Depressionmentioning
confidence: 99%
“…Research Articles 100-90 [89], [74], [51], [53], [64], [101], [66], [54], [2], [56], [57], [77], [70], [75], [58], [80], [81], [44], [52], [45], [93], [65], [34], [62], [63], [86], [99], [87], [88] 89.9-80 [49], [68], [102], [69], [47], [59], [78], [92], [48], [43], [50], [72] 79.9-70 [67], [82], [100], [90], [61], [85], [73], [71] 69.9-60 [79], [91] In 2017, Cai et al presented a journal where he showed a depression identification model comparison between five classifiers on 265 participants where the control participants were 113 and depressed subjects were 152. Among five classifiers (SVM, KNN, DT, LR, R...…”
Section: Accuracy (%)mentioning
confidence: 99%
See 1 more Smart Citation